2004
DOI: 10.1083/jcb.200406060
|View full text |Cite
|
Sign up to set email alerts
|

Presenilin 1 mediates the turnover of telencephalin in hippocampal neurons via an autophagic degradative pathway

Abstract: Presenilin 1 (PS1) interacts with telencephalin (TLN) and the amyloid precursor protein via their transmembrane domain (Annaert, W.G., C. Esselens, V. Baert, C. Boeve, G. Snellings, P. Cupers, K. Craessaerts, and B. De Strooper. 2001. Neuron. 32:579–589). Here, we demonstrate that TLN is not a substrate for γ-secretase cleavage, but displays a prolonged half-life in PS1−/− hippocampal neurons. TLN accumulates in intracellular structures bearing characteristics of autophagic vacuoles including the presence of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
163
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(176 citation statements)
references
References 43 publications
11
163
1
1
Order By: Relevance
“…Intriguingly, cellular phenotypes in PIP 2 -compromised cells are reminiscent of those observed in cells expressing FADassociated presenilin mutations, e.g., ion channel and trafficking deficits (15). The potential role of presenilin in PIP 2 metabolism can be further evidenced by occurrence of PS1 in PIP 2 -enriched subcellular compartments, including lipid rafts (44), phagocytic cups (19), lamellipodia (45), and adherent junctions (18). Thus, our study raises the possibility that PIP 2 may play a key role in the multiple cellular defects associated with presenilin FAD mutations.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Intriguingly, cellular phenotypes in PIP 2 -compromised cells are reminiscent of those observed in cells expressing FADassociated presenilin mutations, e.g., ion channel and trafficking deficits (15). The potential role of presenilin in PIP 2 metabolism can be further evidenced by occurrence of PS1 in PIP 2 -enriched subcellular compartments, including lipid rafts (44), phagocytic cups (19), lamellipodia (45), and adherent junctions (18). Thus, our study raises the possibility that PIP 2 may play a key role in the multiple cellular defects associated with presenilin FAD mutations.…”
Section: Discussionmentioning
confidence: 96%
“…Two of the most consistent cellular changes associated with both PS1 and PS2 FAD-associated mutations include ion channel dysfunction, such as defects in capacitative Ca 2ϩ entry (CCE) (16,17) and membrane trafficking defects, including diminished cell surface delivery of APP (15,(19)(20)(21). These A␤42-independent cellular changes may also contribute to the onset and/or neuropathological characteristics of presenilindependent FAD (22).…”
mentioning
confidence: 99%
“…Reports by Esselens et al (20) and Wilson et al (21) implicated a role of PS1 in the turnover of telencephalin and ␣-and ␤-synucleins, respectively. They showed that these molecules accumulate in degradative organelles resembling autophagosomes in PS1-null neurons, but not by ␥-secretase inhibitor treatment (20,21). Thus, this activity is likely mediated through a ␥-secretase independent mechanism.…”
Section: Ammalian Presenilins (Ps) Consists Of Two Homologous Pro-mentioning
confidence: 99%
“…Other proposed activities of PS that are independent of ␥-secretase include a role in transport of several membrane proteins (34)(35)(36), autophagy and protein degradation (37,38), or act as a scaffold in Erk activation (39,40). However, the dominant phenotype caused by loss of Notch signaling (41)(42)(43) severely limits the ability to identify and interrogate the physiological relevance of the entire spectrum of PS functions.…”
mentioning
confidence: 99%